Tolerance and autoimmunity - Cooke, Anne (Henry Stewart Talks, 2020)
Central and peripheral mechanisms involved in tolerance, Aire as an important transcriptional regulator, The importance of regulatory T cells, The role of inhibitory molecules, Factors than can promote tolerance